PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. WILMAR CAHAYA INDONESIA - Nino Nopriandi (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This study aims to analyze the effect of compensation and motivation simultaneously and partially on employee performance at PT. Wilmar Cahaya Indonesia. The method used is a quantitative method using regression analysis. This study involved 60 research respondents. The results of the study reveal that there is a partial or simultaneous influence of compensation and motivation on employee performance.